Evaluating the Potentials and Problems of CBT Based on PRA Approach in Managing Rural Tourism (Case Study: Torongrejo Village) - Maudina, Annisa Nadhira; Augusty, Widya Rizka; Prasetya, Akhmad Rizkie Ajie (Universitas Diponegoro Publishing Group, Indonesia, 2024)
Torongrejo Village, as one of the villages which developed as new rural tourism by the Batu City Tourism Office, has many attractions, such as nature and local heritage. However, community participation has not been seen in local tourism and still managed individually or privately. One of the alternative concepts to develop rural tourism is community-based tourism (CBT). This study aims to determine the potentials and problems of the village based on the CBT aspects, as follows economic, environmental, cultural, social, and political. In order to achieve these objectives, qualitative method as in Participatory Rural Appraisal (PRA), FGD and field observations were employed and qualitative data collected were analyzed using institutional analysis, evaluation of CBT aspects, and SWOT. This research finds that Cultural and Environmental dimensions are the strengths point, meanwhile politic, economic and social dimensiones are the weak point.